2007
DOI: 10.1536/ihj.48.547
|View full text |Cite
|
Sign up to set email alerts
|

<b>A Case Report of Very Late Thrombosis of Coronary Bare-Metal Stent 10 Years After Stenting</b>

Abstract: SUMMARYAlthough late stent thrombosis is not uncommon with the use of drug-eluting stents, it is unusual with the use of bare-metal stents (BMS) because stent endothelialization is considered to be completed 4 weeks after the intervention. 1)A 64 year-old male had undergone percutaneous coronary intervention (PCI) for a proximal left anterior descending (LAD) artery lesion with a BMS and excellent angiographic results were obtained. Two hundred mg of ticlopidine was prescribed for one month and 100 mg of aspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, a previous study has shown that >30% of patients with BMS in-stent restenosis require hospitalization due to the acute coronary syndrome (ACS) [2]. In addition, the development of atherosclerosis within the neointima has also been a cause of concern [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study has shown that >30% of patients with BMS in-stent restenosis require hospitalization due to the acute coronary syndrome (ACS) [2]. In addition, the development of atherosclerosis within the neointima has also been a cause of concern [3,4]. …”
Section: Introductionmentioning
confidence: 99%